Misanthropoetics : Social Flight and Literary Form in Early Modern England - Darcy, Robert Farquhar (Book collections on Project MUSE., 2021)
Misanthropoetics explores efforts by Renaissance writers to represent social flight and withdrawal as a fictional escape from the incongruous demands of culture.